Antecedents of innovative behavior in public organizations: the role of public service motivation, organizational commitment, and perceived innovative culture - Lee, Geon; Kim, Chulwoo (Frontiers in Psychology, 2024)
Introduction This study examines the dynamics of public service motivation (PSM), organizational commitment, and perceived innovative culture and their collective influence on innovative behavior in public organizations. It uniquely focuses on intrinsic motivational factors, extends the scope of motivational studies to the public sector, and highlights the crucial role of organizational culture in fostering innovation. Methods A web-based survey was administered to 1,021 public servants in the central government of the Republic of Korea. Structured questionnaires were used to collect data, and structural equation modeling (SEM) was employed to analyze the relationships between the variables. Results The SEM results confirmed positive correlations between PSM and both organizational commitment and innovative behavior. However, contrary to expectations, organizational commitment did not significantly predict innovative behavior. Additionally, no mediating effect of organizational commitment was observed. Notably, perceived innovative culture was found to moderate the relationship between PSM and organizational commitment, and between organizational commitment and innovative behavior, particularly in environments with a strong innovation focus. Discussion These findings underscore the significance of PSM in spurring innovative behavior in the public sector, broadening our understanding of intrinsic motivation. This study also accentuates the influence of organizational culture on these dynamics. In practical terms, this suggests the importance of nurturing individuals with high PSM and fostering an environment that balances perceived innovative culture. While contributing to the fields of organizational psychology and public administration, this study has certain limitations and indicates the need for further research in various contexts.